2021
DOI: 10.1111/ssm.12466
|View full text |Cite
|
Sign up to set email alerts
|

Mindset regarding mathematical ability in K‐12 teachers

Abstract: Two potentially impactful conceptions of mathematics and mathematics teaching, teachers' implicit theories (i.e., mindset) toward intelligence and mathematical ability, have not been well examined in the literature. This study established baseline characteristics for these constructs across grades K-12 teachers through a survey of background and mindset characteristics of 583 classroom teachers. Analyses regarding the uniqueness of these constructs, their proportions in the sample of teachers, and differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…According to the theory called "Teacher's Implicit Theory of Professional Abilities," professionals have cognitive, motivational, emotional, and meta-cognitive self-regulating ways that influence teachers' effectiveness in their teaching. Teacher's readiness is one of the factors that allow a teacher to control the learning environment confidently, see the importance of what they are doing, hence, add value, and allow teachers to be flexible and adapt to the changing needs of their students (Willingham et al, 2021). Teacher readiness in Inclusive Education is closely tied to their knowledge, skills, attitudes, and selfefficacy in working with diverse learners.…”
Section: Frameworkmentioning
confidence: 99%
“…According to the theory called "Teacher's Implicit Theory of Professional Abilities," professionals have cognitive, motivational, emotional, and meta-cognitive self-regulating ways that influence teachers' effectiveness in their teaching. Teacher's readiness is one of the factors that allow a teacher to control the learning environment confidently, see the importance of what they are doing, hence, add value, and allow teachers to be flexible and adapt to the changing needs of their students (Willingham et al, 2021). Teacher readiness in Inclusive Education is closely tied to their knowledge, skills, attitudes, and selfefficacy in working with diverse learners.…”
Section: Frameworkmentioning
confidence: 99%
“…Following Claro et al (2016), we chose fixed mindset items only as the use of growth mindset items may have created an acquiescence bias. Considering recent research on teachers (Sun, 2019;Willingham et al, 2021), we found this to be required as a growth mindset may have appeared compelling for adult coaches, resulting in a tendency to drift towards growth mindset answers (Hong et al, 1999). The items were originally developed in English and discussed with Dweck via email correspondence (personal communication, August 21, 2017).…”
Section: Measurementsmentioning
confidence: 99%
“…By using such categorisation, 80% of the sample was expected to be evenly distributed between the fixed and growth A-TM groups, and as only 20% represented a mixed A-TM, they did not represent the extreme groups (Dweck et al, 1995). Furthermore, as research has indicated that some samples may differ from the general population by holding a stronger growth mindset (Sun, 2019;Willingham et al, 2021), we also created a variable based on the work by Claro and Loeb (2019), which used a relative cut-off point based on the A-TM mean score with which fixed A-TM coaches scored below 1 SD, growth A-TM coaches scored above 1 SD, and mixed A-TM coaches scored between ± 1 SD. This was done to examine the variation in mindset scores within the sample.…”
Section: Measurementsmentioning
confidence: 99%
“…Other studies focusing on in-service teachers' mindset mostly explore their presuppositions and biases about the subject matters they are teaching. Willingham et al. (2021), for example, study the mindsets regarding the mathematical ability of 583 K-12 teachers, and find that they display drastically different distributions of mindsets than the population.…”
Section: Literature Reviewmentioning
confidence: 99%